Parental Awareness of the Dangers of Foreign Body Inhalation in Children - Ines Begović; Iva Mihatov Štefanović; Renata Vrsalović; Goran Geber; Elvira Kereković; Tara Lučev; Tomislav Baudoin (Acta Clinica Croatica, 2022)
Background: The presence of a foreign body in the airways is a life-threatening condition and thus a medical emergency that requires timely diagnosis and treatment. If not recognized, it can lead to a number of serious complications. It is of the utmost importance to raise public awareness and educate parents and other caregivers on all aspects of this topic. Methods: This observational cross-sectional study aimed to investigate parental awareness of the dangers of foreign body aspiration. To determine the current level of knowledge of the parents, a 14- question questionnaire was designed and filled out by parents of children under 5 years of age referred for their regular check- ups. Results: The results show that majority of parents know that inhaling a foreign body is a potentially life-threatening condition and recognize which objects have a potential to cause foreign body aspiration. 36.9% of respondents said they knew what the symptoms of foreign body aspiration were, however only 15.6% offered a complete answer. 59.6% of the respondents could not specify the right course of action in case FBA occurred. 2 % responded accurately. No statistically significant correlation was found between the number of children in the family nor the age and the sex of the parents and the level of knowledge about the aspiration of foreign bodies. Conclusion: This study indicates that parents are insufficiently informed on recognizing foreign body aspiration symtoms as well as providing first aid. Media-assisted campaigns and the internet are potential sources of easily accessible educational material.